Judicial Activism and the Protection of Minorities - *, Dr. Razia (IJRDO - Journal of Social Science and Humanities Research, 2016)
This article will highlight the importance of judicial activism in the protection of minorities in India. How the Indian court has over the years expanded and extended the role in interpreting various laws and provisions of the constitution and maintain rule of law in favor of minority communities. The judiciary played an important role in interpreting and brings new laws into existence with change in need of the society. More over as an activist it has over the years become the custodian and guarantor of rights of the minorities a marginalized section, poor and underprivileged sections of the society and made them access to justice by issuing various writs.